2012
DOI: 10.1097/sap.0b013e3182198c55
|View full text |Cite
|
Sign up to set email alerts
|

Usability of the Middle Temporal Vein as a Recipient Vessel for Free Tissue Transfer in Skull-Base Reconstruction

Abstract: In skull-base reconstruction, finding appropriate recipient veins is difficult if the patient has undergone previous craniotomy or requires multiple drainage vessels, because of postoperative scarring and the limited number of veins in the temporal region. Therefore, we have used the middle temporal vein (MTV) to overcome these problems. We examined the presence and caliber of the MTV in 12 patients undergoing skull-base reconstruction. The MTV was identified in all cases and used for reconstruction, alone or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…Anatomic studies done on cadavers have identified an average STA diameter of 1.8 to 2.7 mm before its bifurcation into the frontal and parietal branches. [9][10][11][12][13] Comparable sizes for FA diameter have been reported with values ranging from 2.3 to 2.6 mm at the lower edge of the mandible. 14,15 Whereas smaller than diameters measured in cadavers, our results demonstrate that the two vessels are largely similar within the same patient indicating that vessel size is not a limitation of the STA/V.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Anatomic studies done on cadavers have identified an average STA diameter of 1.8 to 2.7 mm before its bifurcation into the frontal and parietal branches. [9][10][11][12][13] Comparable sizes for FA diameter have been reported with values ranging from 2.3 to 2.6 mm at the lower edge of the mandible. 14,15 Whereas smaller than diameters measured in cadavers, our results demonstrate that the two vessels are largely similar within the same patient indicating that vessel size is not a limitation of the STA/V.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to the STA, the STV has often been considered a secondary or tertiary choice for venous outflow due largely to concerns over caliber and quality. 11,16 However, recent reports document average STV diameters between 2.1 and 3 mm. 17,18 In our series, the median STV diameter was approximately 2 mm, a size that is both usable and reliable.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference between the two means is about half a millimeter (0.57 mm) and would not be considered clinically meaningful The DTV has previously been reported to always course through the superficial temporal fat pad, which has been considered a reliable anatomical landmark for identifying the vessel (Henry et al, 2012;Jung et al, 2014;Tansatit et al, 2015;Yano et al, 2012;Yano et al, 2014). The type VII sub-variant identified in our study instead courses posteriorly to the superficial temporal fat pad.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MTV has been frequently selected as the recipient vein to improve the success rate of temporal vascular anastomosis in our institution, and its effectiveness has been demonstrated. 9,10 The MTV courses below the superficial layer of the deep temporal fascia and is distributed in the superficial temporal fat pad between the superficial and deep layers of the deep temporal fascia. 11 The MTV runs approximately parallel in a line between the lateral edge of the zygomatic arch and the eyebrow and joins the main trunk of the STV at the level of the zygomatic arch.…”
Section: Discussionmentioning
confidence: 99%